THE APPLICATION OF DIFFERENTIAL GAMES IN THE SYSTEM OF SUPPORTING INVESTMENT DECISIONS FOR DIGITAL PROJECTS - Kartbaev , Т.С.; Ismailov , А.Е.; Turgynbaeva , А.А.; Kerimbaeva , В.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article presents a model of a decision support system for investments in enterprise digitalization projects, taking into account multiple factors. The model is based on the theory of nonlinear differential games, which makes it possible to formalize the process of opposition between investors making decisions under conditions of uncertainty and competition. The developed approach allows for finding rational financing strategies using a numerical solution through the Runge–Kutta method. Computational experiments were carried out for models with constant and variable parameters. The results confirm the effectiveness of the proposed model for supporting investment decisions in the field of enterprise digital transformations. In this article, considering multiple factors, the possibility of implementing continuous investments in enterprise digitalization projects is examined. The paper, aimed at solving this problem, is of both scientific and practical relevance. Taking into account the multifactorial nature, a class of nonlinear differential games was considered, which made it possible to accurately describe the investment process in enterprise digitalization projects. This enables the investor to analyze and identify rational investment strategies.